Implementasi Aplikasi “ngaji.ai” dalam Pembelajaran Al-Qur’an - Salsabila, Isma Aina; Atikoh, Nurul (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research examines the implementation of artificial intelligence (AI) in studying the Qur'an. The Qur'an has an important role, namely as a source of knowledge that covers all aspects of human life. Artificial intelligence can help education by improving learning and teaching. This research uses a case study method with a descriptive qualitative approach. With descriptive qualitative methods, it is hoped that data can be explored more deeply about the topics discussed in the research. The research results reveal the application of “ngaji.ai” allows students to learn at their own pace and in accordance with the guidance of the Subject Teacher (Islamic Religious Education) without being limited by place and time. The